Green bridge between waste and energy: conversion the rotten wood into cathode for functional Zn-air battery. (20th August 2022) - Han, Shengbo; Peng, Shaomin; Gao, Zihan; Sun, Ming; Cheng, Gao; Zhang, Hao; Su, Xiaohui; Chen, Meijie; Yu, Lin
Highlights: A simple method is provided for converting waste biomass into N-doped biochar. The as prepared catalyst with similar ORR performance than that of Pt/C. Different types of ZAB are assembled to power homemade electronics. The button cell shows outstanding performance than commercial PR 48 (Panasonic). Abstract: Oxygen reduction reaction (ORR) is a cathode reaction for Zn-air battery (ZAB), however, it limits the large scale utilization of ZAB for its nature of a slow dynamic process. Therefore, it is of great practical significance to improve ORR performance when waste biomass materials are turned into cathode materials for ZAB. Herein, we report a simple and expandable green strategy, that can convert waste biomass materials (rotten wood (RW)) into N-doped carbon material (NRW-1000) with excellent ORR ability in a one-step process. In this strategy, NH4 Cl is selected as activator and N source, thus realizing the biomass carbonization, activation and N doping process at the same time. The NRW-1000 prepared by this strategy was endowed with a half-wave of 0.87 V ( vs. RHE), which is the same as Pt/C (0.87 V). To test the practicality of NRW-1000, different types of ZAB were assembled to power homemade electronics. Remarkably, the button ZAB based on NRW-1000 showed even more impressive energy density (58.52 mW cm −2 ) than that of the commercial PR 48 (Panasonic) (30.73 mW cm −2 ). Our work provides a solution to the current energy crisis by recycling waste into electrochemical catalysts. Graphical abstract: Image, graphical abstract